Exposição aguda ao HGCL2 induz os receptores ERα e ERβ a agirem como vasoconstritores e promove denudação endotelial através da via de sinalização PI3K/AKT - Cordeiro, Evellyn Rodrigues (2019)
Cardiovascular diseases are more frequent among postmenopausal women due to the decline in the estrogen plasma concentration, evidencing the important role of vascular modulator that this hormone exerts. The regulation of vascular reactivity by estrogen receptors is mainly related to the maintenance of normal endothelial function. However, its vascular modulatory effects are controversial, since they also occur in pathological conditions in women who use oral contraceptives and hormone replacement. As mercury is widely associated with the development of cardiovascular diseases, we investigated putative hazardous effects on the mechanisms that modulate vascular reactivity in aortic rings of female Wistar rats promoted by acute HgCl2 exposure (6 nM) for 45 minutes. Mercury increased oxidative stress and vascular reactivity stimulating NADPHoxidase, COX-2 activity and production de thromboxane A2 (TXA2). The metal also induced endothelial denudation in the aorta, evidenced by scanning electron microscopy, by reducing the bioavailability of nitric oxide (NO) and enhancing the activity of the PI3K/Akt signaling pathway. In addition to the above, our results suggest that mercury activates mechanisms that stimulate vasoconstriction via nuclear estrogen receptors (ERα, ERβ). Our results suggest that mercury may increase the chances of developing cardiovascular disease in women by increasing oxidative stress, reducing NO bioavailability, increasing TXA2 production, and altering the functioning of ERα and ERβ, and should be considered an important environmental risk.